Business Design And Implementation Report Organic Layer Farming Business - Teguh Yudhotomo (Cita konsultindo, 2024)
Livestock is one of the important sectors in the Indonesian economy. One form of economic sector that can be established is Yudho's Farm laying hens farm. This final project is an implementation report of the business design implementation. The establishment of Yudho's Farm business was motivated by the unrest faced by consumers regarding the increasing price of eggs and the unstable quality of eggs. In addition, the problems faced by the author are difficulties in terms of maintenance and cost efficiency. Chicken care is quite difficult and quite expensive, such as the cost of vaccines, medicines and maintenance costs if the chicken is sick.With the existing problems, Yudho's Farm intends to make an innovation, namely the use of organic herbs. Based on previous research, it shows that the use of organic herbs in chickens serves to maintain chicken health, increase productivity and improve egg quality. In addition, the impact felt from the use of organic herbs is that it can save operational costs because the herbal ingredients used include natural ingredients that are easily available and cheap and can replace the function of vaccines. Yudho's Farm is located in Cilacap, Central Java. Observation and data collection were carried out by observation for 6 months. Yudho's Farm product distribution is carried out offline to the community and orders can be made online through social media, namely whatsapp. Marketing is done through sales to grocery stores to reach consumers. The problems faced during the implementation of this business are delays in product preparation and marketing to consumers due to limited human resources and inadequate capital.